Steels : microstructure and properties. - Bhadeshia, H. K. D. H. 1953-; Honeycombe, R. W. K. (Butterworth-Heinemann, 2017)
Steels: Structure and Properties, Fourth Edition is an essential text and reference, providing indispensable foundational content for researchers, metallurgists, and engineers in industry and academia. The book provides inspiring content for undergraduates, yet has a depth that makes it useful to researchers. Steels represent the most used metallic material, possessing a wide range of structures and properties. By examining the properties of steels in conjunction with structure, this book provides a valuable description of the development and behavior of these materials-the very foundation of their widespread use. The new edition has been thoroughly updated, with expanded content and improved organization, yet it retains its clear writing style, extensive bibliographies, and real-life examples.
Keywords: Steel.; Steel -- Metallurgy.; Steel -- Metallography.; elektronické knihy; electronic books